Investigating the behavior of an expansive soil slope in critical linear infrastructure in China using multi-temporal InSAR - Jiang, Zhen; Wu, Zigui; Li, Ziyuan; Hu, Jun; Wu, Yuwei; Ou, Liye; Zhang, Tongyuan (Frontiers in Environmental Science, 2023)
The one of the most significant linear infrastructures in China is the Middle Route of the South-to-North Water Diversion Project (MR-SNWDP), in which a large part of sections is constituted of expansive soil slope (ESS) that threatens the canal's safety. Here, we prepare 144 Sentinel-1 data from May 2017 to July 2022 to study the ESS's behavior in the case of the canal section in Huixian City in the MR-SNWDP. Then, the Elastoplastic Deformation model under Wetting and Heating Effects (EDWHE) is employed to characterize ESS's displacement accurately. As the InSAR results illustrate, the unstable zones tend to be small and distributed along the canal slope, with the magnitude of deformations generally no more than 20 mm/year. And their deformation time series generally accumulate exponentially and evolve in a significant pattern of seasonal swelling and shrinkage. We observe that the slope movements significantly accelerated during the period when an extreme rainfall occurred near July 22, 2021. Affected by satellite imagery and geometric structure of the slope, the magnitudes and evolving trends of LOS deformation vary with different aspects of the slope sections. Then, the elastic swelling-shrinkage deformations are derived through the EDWHE model, of which the uplift or settlement is mainly up to geological and meteorological conditions. Moreover, the active zone depths of the ESS are retrieved using an InSAR-based lag time approach, clearly reflecting their distribution pattern. With the works, the behaviors of ESS in the study area are quantitatively analyzed using InSAR, and the results provide supports to design protective slope treatments and keep the canal safe in the MR-SNWDP.